(untitled) (ACME, 2023)
The increasing prominence of men’s studies in the academic panorama has allowed for further investigation not only on women’s, but also on men’s literary identities. The Ibis Trilogy by Amitav Ghosh offers new insights on the subject by staging several queer masculinities. The present essay analyses the non-conforming identity of Kesri Singh from the perspective of men’s studies. Firstly, the essay compares and contrasts the socially imposed masculinity with Kesri’s divergent one. Secondly, it highlights the strategy deployed by the warrior in order to protect his psychological and physical integrity in a toxic environment. Given the strong historical background of the novels, references are provided to account for the patriarchal context in which Kesri develops. Further sources of discrimination such as race and class are also explored, according to an intersectional feminist approach. Thus, it will be proved that a male gender related discourse covers ample narrative space in the Trilogy; it also reflects the critical opposition by Ghosh to the Western colonialism and Indian caste division. Moreover, it will be exposed the manipulative use of the male gender as an instrument to enforce colonialism and classism. Therefore, the Trilogy presents masculinity as a highly debatable, multifaceted notion which undergoes a negotiation in meaning throughout the novels. This premise leads to a broader definition of the concept, which provides a new, significant viewpoint on the subject.